Essays in Argentine Labour History, 1870-1930 - Adelman, Jeremy. author. aut Link
XV, 243 p.
Keywords: From 1870 to 1930 Argentina underwent massive changes. The development of the working classes shaped the direction of those changes by promoting democratization and economic redistribution. This text looks at the formation and weaknesses of the Argentine working classes during this period.